2019
DOI: 10.3168/jds.2019-16672
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effects of porcine plasma or combined sodium butyrate and Bacillus subtilis on growth and health of grain-fed veal calves

Abstract: The objective of this study was to evaluate the effects of incorporating 2 commonly used additives or spray-dried porcine plasma in calf milk replacer (CMR) on calf performance and health. Male Holstein calves (n = 158) transported from auction barns and local dairy farms were randomly assigned to receive 1 of 3 decoquinate-containing CMR for the first 49 d of the experiment: all milk protein and no additives (CONT); 15% of crude protein (CP) replaced with spray-dried porcine plasma, no additives (PLM); or all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
(23 reference statements)
2
10
0
Order By: Relevance
“…This finding is consistent with Morrill et al (1995), who observed improved BW gains when feeding SDP. Conversely, Morrison et al (2017a) and Wood et al (2019) found no differences in ADG when feeding diets containing levels of SDP similar to those in the current study. Increasing SDP had contrasting effects on frame growth parameters, with increasing SDP leading to an increase in withers height and tending to lead to an increase in withers height ADG but a decrease in body length and hip width (Table 5).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This finding is consistent with Morrill et al (1995), who observed improved BW gains when feeding SDP. Conversely, Morrison et al (2017a) and Wood et al (2019) found no differences in ADG when feeding diets containing levels of SDP similar to those in the current study. Increasing SDP had contrasting effects on frame growth parameters, with increasing SDP leading to an increase in withers height and tending to lead to an increase in withers height ADG but a decrease in body length and hip width (Table 5).…”
Section: Discussionsupporting
confidence: 72%
“…However, these studies used MR formulations with lower overall CP contents and fed at a lower plane of nutrition. Wood et al (2019) fed an MR with protein and fat contents similar to the ones used in this study and replaced 15% of skim milk-based protein with SDP; they found no differences in growth or medication level but did find a decrease in severe scours.…”
Section: Discussionmentioning
confidence: 57%
“…Multispecies probiotics [Lactobacillus acidophilus (McFarland et al, 2018;Łukasik and Szajewska, 2018), Bacillus subtilis (Rui and Ma, 2020), Saccharomyces cerevisiae (Thévenot et al, 2015)] have achieved certain results in human application, and there are similar reports in animals. Studies have found that Lactobacillus acidophilus (Sharma et al, 2018), Bacillus subtilis (Sun et al, 2010;Zhang et al, 2017;Wood et al, 2019), and Saccharomyces cerevisiae (Fomenky et al, 2018;Villot et al, 2019) can improve calf growth performance by improving immune function and balancing the structure of intestinal microbiota. The objectives of this study are: (1) To evaluate whether MSP supplementation can reduce the incidence of diarrhea in pre-weaning calves while improving the growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…Enteric disease challenge was greater in these other studies. Significant respiratory disease challenge did occur in this trial (65% of calves were treated for respiratory disease) but feeding spray-dried porcine plasma (Wood et al, 2019) or spray-dried bovine plasma (Wood et al, 2013) to calves has not been shown to affect its incidence.…”
Section: Effect Of Porcine Plasma On Growth and Health Of Holstein Calvesmentioning
confidence: 71%
“…In studies using SDPP, it has been shown to reduce calf mortality and days with diarrhea when used at 5% inclusion in the formula, replacing 20% of the CP compared with a whey protein concentrate-based formula (Quigley and Wolfe, 2003). In addition, when replacing 15% of whey-based proteins, SDPP was shown to reduce the severity of diarrhea and provide comparable performance (Wood et al, 2019).…”
Section: Jdsmentioning
confidence: 99%